Maximizing utilization of alfalfa protein: The example of the lactating dairy cow - Broderick G.A. (Quality in lucerne and medics for animal production, 2001)
Evidence from numerous feeding studies with lactating dairy cows indicates that excessive rumen protein degradation makes absorbed protein the most limiting nutritional factor in higher quality temperate legume forages, especially alfalfa. Extensive NPN formation in ensiled alfalfa depresses protein utilization. Techniques that reduce NPN formation in the silo, such as field wilting or acid treatment will enhance protein value to the lactating cow. However, more effective means of reducing NPN in alfalfa silage are needed. The CP in alfalfa harvested as hay, rather than silage, is used more efficiently by lactating cows; degraded CP from hay is captured more efficiently by rumen microbes for protein synthesis in vitro. Maximizing concentrate intake without over feeding will stimulate microbial utilization of degraded protein in the rumen. Supplementation of alfalfa based diets with high 'bypass' proteins has resulted, in some cases, in substantial increases in milk production with cows in early lactation.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)